Molecular characteristics of a novel recombinant of porcine epidemic diarrhea virus - Nefedeva, Mariia (Arch Virol, 2019)
Porcine epidemic diarrhea (PED) is a contagious viral disease in pigs, caused by the coronavirus porcine epidemic diarrhea virus (PEDV). PEDV infection results in significant mortality in piglets in unvaccinated herds. Like many others RNA viruses, PEDV has high evolutionary rate and is prone to genetic mutations. In this study, we analyzed the complete genome sequence of the recently sequenced isolate PEDV/Belgorod/dom/2008. A recombination event in S gene of PEDV/Belgorod/dom/2008 was detected. Pairwise identity analysis of the whole genome sequences revealed that PEDV/Belgorod/dom/2008 is an intermediate between PEDV and transmissible gastroenteritis virus (TGEV) strains. These results can be used for further analysis of the evolutionary variability, prevalence, and epidemiology of the porcine epidemic diarrhea virus.